Ответ: х = -5
Объяснение:
[tex]5(x+2)^{2} +(2x-1)^{2} = 22+9(x-3)(x+3)\\5(x^{2} +4x+4)+4x^{2} -4x+1 = 22+9(x^{2} -9)\\5x^{2} +20x+20+4x^{2} -4x+1 = 22 +9x^{2} -81\\[/tex]
приводим подобные:
[tex]9x^{2} +16x+21 = 9x^{2} -59[/tex]
переносим через знак равно, меняя знак на противоположный:
[tex]9x^{2} +16x - 9x^{2} = - 59-21[/tex]
[tex]16x= -80\\x=-5[/tex]
[tex]\displaystyle\bf\\5(x+2)^{2} +(2x-1)^{2} =22+9(x-3)(x+3)\\\\5\cdot(x^{2} +4x+4)+(4x^{2} -4x+1)=22+9\cdot(x^{2} -9)\\\\5x^{2} +20x+20+4x^{2} -4x+1=22+9x^{2} -81\\\\9x^{2} +16x+21=9x^{2} -59\\\\9x^{2} +16x-9x^{2} =-59-21\\\\16x=-80\\\\x=-5[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: х = -5
Объяснение:
[tex]5(x+2)^{2} +(2x-1)^{2} = 22+9(x-3)(x+3)\\5(x^{2} +4x+4)+4x^{2} -4x+1 = 22+9(x^{2} -9)\\5x^{2} +20x+20+4x^{2} -4x+1 = 22 +9x^{2} -81\\[/tex]
приводим подобные:
[tex]9x^{2} +16x+21 = 9x^{2} -59[/tex]
переносим через знак равно, меняя знак на противоположный:
[tex]9x^{2} +16x - 9x^{2} = - 59-21[/tex]
[tex]16x= -80\\x=-5[/tex]
[tex]\displaystyle\bf\\5(x+2)^{2} +(2x-1)^{2} =22+9(x-3)(x+3)\\\\5\cdot(x^{2} +4x+4)+(4x^{2} -4x+1)=22+9\cdot(x^{2} -9)\\\\5x^{2} +20x+20+4x^{2} -4x+1=22+9x^{2} -81\\\\9x^{2} +16x+21=9x^{2} -59\\\\9x^{2} +16x-9x^{2} =-59-21\\\\16x=-80\\\\x=-5[/tex]